PENGARUH FAMILY CONTROL TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA SEKTOR PROPERTI DAN REAL ESTATE - Limbago, Elsa (Business Accounting Review, 2014)
The majority of companies listed in Indonesia Stock Exchange are family firms that have advantages and disadvantages that affect the performance of the companies. According to many previous researches about the influence of family control, there were still many unconsistent results. This study aimed to know the influence of family control on profitability and firmâs value. Profitability was measured by using ROA and firmâs value by using Tobinâs Q. The Control variables used were size, sales growth, and leverage. The sample used in this research were firms in the sector of property and real estate industry which fulfilled certain criteria and analysed by using multiple regression analysis.The results proved that the family control had significant affect on profitability but not the firmâs value. The size and sales growth variables had significant affect on profitability but not on the firmâs value. Meanwhile, leverage variable had no affect on the profitability but had significant positive affect on the firmâs value.